About Macrophya parvula and larvae of several Central European Macrophya (Hymenoptera: Tenthredinidae) - Macek, Jan (Zootaxa, 2012)
The adults of both sexes of Macrophya parvula (Konow, 1884) are described and illustrated, the male for the first time. The larvae of Macrophya blanda (Fabricius, 1775), M. rufipes (Linné, 1758), M. diversipes (Schrank, 1782), M. parvula, M. recognata Zombori, 1979 and M. erythrocnema Costa, 1859 are described and illustrated for the first time. The larvae of M. annulata (Geoffroy, 1785), M. militaris (Klug, 1817) and M. montana (Scopoli, 1763), which have been described previously, are diagnosed. New data on the biology of all these species, including host plants, are provided.